PERAN DEWAN KOMISARIS INDEPENDEN DAN KERAGAMAN BUDAYA DEWAN KOMISARIS MEMODERASI HUBUNGAN ANTARA KEBERAGAMAN GENDER DEWAN KOMISARIS DAN PENGUNGKAPAN ESG - Fauzan, Muhammad; Zaitul, Zaitul; Ilona, Desi (Gapenas Publisher, 2025)
This study aims to empirically examine the effect of gender diversity on the board of commissioners on ESG disclosure, with cultural diversity and independent commissioners as moderating variables, and three control variables, namely leverage, firm size, and firm age, in LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2023–2024, using a purposive sampling method. A total sample of 42 companies was obtained. The type of data used in this study is secondary data obtained from www.idx.co.id and company websites. The data were analyzed using SPSS and Gretl software. The empirical findings of this study provide evidence that gender diversity on the board of commissioners has a negative effect on ESG disclosure. Cultural diversity and independent commissioners do not have a negative effect on ESG disclosure. Gender diversity on the board of commissioners has no effect on ESG disclosure when moderated by cultural diversity. Furthermore, gender diversity on the board of commissioners has no effect on ESG disclosure when moderated by independent commissioners